Idiopathic multilocular thymic cyst-an incidental anterior mediastinal mass - S., Sowmya; Mohanraj, Anbarasu; Raman, Karthik; Mohandoss, Bharath Kumar (International Journal of Research in Medical Sciences, 2019)
Acquired thymic cyst are multilocular and they occur de novo or in association with mediastinal neoplasm, systemic autoimmune diseases and trauma. Here, we report a case of acquired multilocular thymic cyst due to non-specific inflammatory etiology in a 42-year old gentleman and our approach to diagnosis and management of anterior mediastinal mass. With no specific clinical symptom, he was diagnosed with anterior mediastinal mass incidentally by imaging studies. Definitive diagnosis of multilocular thymic cyst was obtained by tissue diagnosis of the anterior mediastinal mass resected during the surgery.